Developing Student-Inclusive Characters Through Al-Quran and Ḥadīth - Hudzaifah Achmad Qotadah; Adang Darmawan Achmad; Iqbal Syafri; Abdurrahman Achmad Al-Anshary; Ma’isyatusy Syarifah (UIN Sunan Gunung Djati Bandung, 2022)
Education is a fundamentally important social activity, and its major objective is to improve the social environment. Therefore, education that focuses on establishing an inclusive and open attitude, particularly in matters of religion, is essential, particularly in the lives of people who live in a society with a varied range of beliefs and practices. Hence, the primary objective of this research is to analyze how developing student-inclusive characters through learning Quran and ḥadīth. The research employed a full qualitative method and data documentation through the semi-structured interview method by using Bahasa Indonesia, which was then analyzed descriptively. The interview took place at MAN 1 Yogyakarta and it involved various participants. Based on the findings of the research, it is possible to develop student-inclusive characters through the study of Quranic verses and ḥadīth texts by employing three practices; the historical approach, values examination, and case analysis. Thus, students will confidently be able to form groups of individuals who live in harmony, and it may provide a means of resolving various problems and hatred.